The Influence of Money Politics on the Political Choices of the Buduran District Community in the East Java Gubernatorial Election - Nesta Imanuel Christian; Jhezkiel Enrico Laksmana (PT Pro Panoramic Solution, 2025)
In the context of the gubernatorial election in East Java, this study examines how the political choices of the public are influenced by money politics. Money politics in a democratic system often affects voters' decisions, raising concerns about the integrity and quality of the electoral process. This research employs a qualitative approach through in-depth interviews and surveys to explore how voters react to offers of money politics and the consequences for their attitudes and behaviors when casting their votes. The study finds that although many voters are aware of the negative impacts of money politics, many accept the proposals due to economic reasons and pressing needs. Furthermore, the practice of money-focused politics often diverts voters' attention from candidates' goals and visions to the financial incentives offered. The findings of this research emphasize that, to ensure fairer and higher-quality elections in the future, voter education and strengthened regulations are necessary to combat the practice of money politics.